2013
DOI: 10.1080/03601277.2012.734162
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards and Limitations to ICT Use in Assisted and Independent Living Communities: Findings from a Specially-Designed Technological Intervention

Abstract: While much literature has been devoted to theoretical explanations of the learning processes of older adults and to the methods of teaching best utilized in older populations, less has focused on the education of older adults who reside in assisted and independent living communities (AICs), especially with regards to information and communication technology (ICT) education. The purpose of this study is to determine whether participants’ attitudes and views towards computers and the Internet are affected as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 29 publications
1
37
1
Order By: Relevance
“…Also, with the growth in medical devices that interface with smart phones or tablets, increased digital literacy may enable older adults to be more proactive in their own health care. Therefore, it would be beneficial for older adult advocacy groups or the government to provide digital literacy learning support to help older adults when they have questions or problems (Berkowsky et al, 2013; Cotten, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, with the growth in medical devices that interface with smart phones or tablets, increased digital literacy may enable older adults to be more proactive in their own health care. Therefore, it would be beneficial for older adult advocacy groups or the government to provide digital literacy learning support to help older adults when they have questions or problems (Berkowsky et al, 2013; Cotten, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Past studies found that lacking “relevance” and “relative advantages” influence whether older adults use computers (Mitzner et al, 2010; Selwyn, Gorard, Furlong, & Madden, 2003). The fear of computers or other new technologies can stop them from using new technologies (Berkowsky, Cotten, Yost, & Winstead, 2013; Haederle, 2011). However, studies also showed that older adults would learn to use technology if they are given at least some opportunity (Cody et al, 1999; Winstead et al, 2012).…”
Section: Digital Literacy and Older Adultsmentioning
confidence: 99%
“…Coupled with this change in demographics, the past decades have witnessed a substantial increase in the use of technology in all aspects of daily living. Various studies are being conducted and thousands of new technologies are being developed to remedy issues that older adults might experience regarding physical and mental abilities, and eventually improve their quality of life [2,3]. Recently, as an alternative technology for older adults, positive technology has emerged and is receiving attention.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet and information and communications technologies (ICTs) have significantly advanced over time and are pervasive in most areas of life (Struve & Wandke, ; Wagner, Hassanein, & Head, ). ICTs include any computer‐based device or application used for communication and information purposes, such as Internet‐connected computers or tablets (e.g., iPads®), mobile communication devices (e.g., smartphones), and social media applications (e.g., email, video calling or conferencing, Facebook™; Berkowsky, Cotton, Yost, & Winstead, ; Woodward et al, ).…”
mentioning
confidence: 99%
“…Older adults (i.e., individuals 65 years and older) are less likely to use the Internet and ICTs than younger individuals. Several factors may influence older adults' use (or lack thereof ) of the Internet and ICTs, including: misconceptions about the Internet and ICTs being too difficult (Berkowsky et al, 2013;Morris et al, 2007), safety and privacy concerns (Cresci et al, 2010), health declines (Carpenter & Buday, 2007;Wagner et al, 2010), income and education constraints (Carpenter & Buday, 2007;Cresci et al 2010;Morris et al, 2007;Woodward et al, 2011), and continuous technological advancements that may make it difficult for older adults to keep pace with these technologies (Heaggans, 2012).…”
mentioning
confidence: 99%